2013
DOI: 10.4018/jgcms.2013010105
|View full text |Cite
|
Sign up to set email alerts
|

Using a Ludic Simulation to Make Learning of Middle School Space Science Fun

Abstract: In this paper, the authors describe a ludic simulation designed for middle school space science and examine its use to support students’ learning and motivation. The participants were 383 sixth graders and 447 seventh graders. The findings of this study showed that sixth- and seventh-graders perceived the simulation as having substantial ludic characteristics and educational value. The results indicated that having a playful experience is important for this age group and that participating in a ludic simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Ninety-five percent of the 84 coded responses indicated the students enjoyed the PBL experience (see Table 5 and Figure 5), because they had learned knowledge and skills and the experience was "fun. " Having fun while learning is a consistent theme from both open-ended questions and interview responses (Liu, Horton, Kang, Kimmons, & Lee, 2013). Our previous research examining student attitude toward science and their achievement using Alien Rescue with regular education students also found a positive relationship (Kimmons et al, 2012).…”
Section: Attitude and Learning By At-risk Studentsmentioning
confidence: 62%
“…Ninety-five percent of the 84 coded responses indicated the students enjoyed the PBL experience (see Table 5 and Figure 5), because they had learned knowledge and skills and the experience was "fun. " Having fun while learning is a consistent theme from both open-ended questions and interview responses (Liu, Horton, Kang, Kimmons, & Lee, 2013). Our previous research examining student attitude toward science and their achievement using Alien Rescue with regular education students also found a positive relationship (Kimmons et al, 2012).…”
Section: Attitude and Learning By At-risk Studentsmentioning
confidence: 62%
“…Numerous learning benefits of game-based approaches are summarized in Table 1. Game-based learning has been successfully applied in various fields including marketing (Daly, 2001;Hamer, 2000), information systems (Massey, Brown, & Johnston, 2005), international business (Paul & Mukhopadhyay, 2004), business administration (Elgood, 1997), engineering (Hsiung, 2012;Prince, 2004), computer science (Martocchio & Webster, 1992;Papastergiou, 2009), mathematics (Carr, 2012), space science (Liu, Horton, Kang, Kimmons, & Lee, 2013), and physics (Eseryel, Law, Ifenthaler, Ge, & Miller, 2014;Squire, Barnett, Grant, & Higginbotham, 2004).…”
Section: Game-based Experiential Learningmentioning
confidence: 99%
“…The results of the study indicated a 20 percentile increase in students' achievement. Liu, Horton, Kang, Kimmons, and Lee (2013) support that games are beneficial to learning, and claim that you should not make a game too hard. In their research they found that middle school students learn better in playful environments.…”
Section: Literature Reviewmentioning
confidence: 96%